Effectiveness of Giving Dragon Fruit and Fe Tablets on Increasing Hemoglobin Levels in Pregnant Women - Putri, Melia Dwi Yitna; Zahra, Tamela (Journal of Health, Medicine and Nursing, 2024)
In 2018, the WHO reported that 41.8% of maternal deaths in developing countries were associated with anemia. Increasing hemoglobin levels can be supported by consuming fruits rich in iron, folic acid, and vitamin C, with dragon fruit being one of the beneficial options. This study aimed to assess the effectiveness of dragon fruit and Fe tablets in raising hemoglobin levels among pregnant women in Puluhan Village, Trucuk District, Klaten Regency. Utilizing a literature review approach, the study involved searches across PubMed and Google Scholar, using keywords such as "Dragon Fruit Juice," "Fe Tablets," "Hb Levels," and "Pregnancy." From 2020 to 2023, four relevant journals were identified and analyzed. Participant characteristics showed that most were aged 20-35 years (80%), with a high school education level (35%), predominantly homemakers (65%), multiparous (50%), and had a gestational age of less than 37 weeks (65%). The average Hb level before receiving dragon fruit and Fe tablets was 11.40 g%, which rose to 11.72 g% after the intervention. Thus, the provision of dragon fruit and Fe tablets was found to have a positive effect on hemoglobin levels in pregnant women..